THE CONSUMER BEHAVIOR ANALYSIS OF WEEABOO: PURCHASE DECISION MAKING PROCESS ON JAPANESE POPULAR CULTURE PRODUCTS - Septiar, Egi; Wisesa, Anggara (Journal of Business and Management, 2017)
Abstract. Weeaboo is a non-Japanese person who is obsessed with the Japanese cultural world. From the results of preliminary research, it is found that understanding the characteristics of weeaboo is very important because it implies the emergence of a gap between Japanese popular culture products provided with weeaboo expectations as consumers. This research focuses only on the analysis of weeaboo consumer behavior that was derived from the identification of the influencing factors and the purchase decision making process towards Japanese popular culture products. This research applied Kotler and Keller Stimulus-response models to assist the data analysis. Narrative method used in this research and in-depth interview is the way to collecting data. Meanwhile, to interpret the obtained data using components of data analysis: Interactive model by Miles and Huberman. The culture of watching anime and visiting Japanese events becomes a trigger a weeaboo in the purchase of Japanese pop culture products which is shown by the purchase of anime products such as t-shirts, jackets, bags, anime figures, pins, key chains and posters. The purchase of Japanese popular culture products is also a representation of the personality and self-concept of a weeaboo in their reference group. The character of weeaboo that is vary has implications for the grouping of sales targets that can address the product nonconformance issues provided with the products weeaboo is expected to be consumers. The research found that the weeaboo classification based on the purchasing behavior was based on five categories: weeaboo Japanese pop culture, weeaboo Japanophile, weeaboo J-fashion, weeaboo cosplayer and weeaboo Sultan. This research suggests that sellers of Japanese popular culture products should look at the rational and emotional weeaboo purchasing behavior that indirectly impacts the marketing strategy. In addition, the manufacture of products must always be up to date on the latest anime and optimization of promotions in Instagram and Facebook due to changes in consumer behavior that search more for product information in social media.Ã‚Â Keywords: Weeaboo, Japanese pop culture, Consumer Behavior, Purchase Decision, Qualitative Research